Hypertrophic cardiomyopathy and atrial fibrillation: the Cardiomyopathy/Myocarditis registry of the EURObservational Research Programme of the European Society of Cardiology. (3rd October 2022) - Mizia-Stec, K; Gimeno Blanes, J R G; Charron, P; Elliott, P; Kaski, J P; Maggioni, A L; Tavazzi, L; Tendera, M; Wybraniec, M T; Caforio, A
Abstract: Background: Current guidelines for AF management underline a complex approach to detecting and treating atrial fibrillation (AF). Hypertrophic cardiomyopathy (HCM) is commonly associated with AF. Purpose: To assess the clinical characteristic and prognosis in patients with HCM and AF. Methods and results: Overall, 1739 adult patients with HCM (711/40.9% female; median age at diagnosis: 55.5 years) were enrolled in the EURObservational Research Programme – Cardiomyopathy/Myocarditis Long-Term Registry. Baseline clinical characteristics and adverse cardiovascular endpoints at 1-year follow-up were analysed. Results: At baseline, AF was found in 478 (27.5%) subjects (paroxysmal: 54.7%, persistent: 17.6%, permanent: 27.7%). Newly diagnosed AF was identified during 1-year follow-up in 48 (2.8%) subjects with HCM. The presence of AF was associated with higher age (59.6±13.8 vs 50.8±16.1, p<0.001); BMI (27.7±5.1 vs 26.6±4.6 kg/m 2, p<0.001); more advanced NYHA class (NYHA I/II and III/IV: 75.1 and 24.9 vs 86.2 and 13.8%, p<0.001); more frequent history of diabetes (14.6 vs 8.4%, p<0.001); arterial hypertension 43.4 vs 34.6%, p<0.001); renal impairment (15.4 vs 6.35%, p<0.001); and history of sustained VT (10.8 vs 6.35%, p<0.001). AF patients were characterized by lower left ventricular ejection fraction (LV EF) (59±12 vs 63±11%, P<0.001), left atrium (LA) dilatation (48.9±9.1 vs 42.4±7.7%, p<0.001), increased pulmonary artery systolic pressure (37.8±13.7 vs 29.6±12.6 mmHg, p<0.001), distribution of LV hypertrophy (p=0.032) and more advanced LV diastolic dysfunction (p<0.001). On multivariate logistic regression analysis, independent predictors of AF in the HCM population were: age at enrolment (OR 1.068, P<0.001); LVEF (OR 0.978, p<0.001); and LA diameter (OR 1.094, p<0.001). Oral anticoagulation (OAC) was administered in 69.5% of patients with AF (vitamin K antagonist: 48.5%; direct OAC: 21%). ICD was implanted in 26.8% in AF and 16.9% in non-AF subjects (p<0.001). PVI was performed in 9.9% of AF patients only. The annual incidence of stroke/TIA was higher in AF than in the non-AF population (2.64 vs 0.85%, p=0.009). There was a trend towards increased death from any cause in the AF population (3.39 vs 1.74%, p=0.05). There were no differences in SCD-risk score between AF and non-AF subjects. Conclusion: The study reveals a high prevalence of AF in patients with HCM that corresponds with more advanced symptoms, increased prevalence of comorbidities, structural and functional heart remodelling along with inadequate anticoagulation and a significant increase in the risk of stroke. The clinical characteristics of HCM-AF patients indicate that the ESC recommended complex AF approach "CC To ABC" is appropriate in this population. Funding Acknowledgement: Type of funding sources: None.